Cross-lagged relations among linguistic skills in european Portuguese: A longitudinal study - Santos, Sandra (2020)
Research has widely demonstrated the contribution of word reading, listening comprehension skills, and oral reading fluency to reading comprehension performance. However, the existence of reciprocal relations among these skills has been investigated less frequently. The authors examined the directionality of the relations among reading comprehension, listening comprehension, word reading, and oral reading fluency in Portuguese elementary school students from second to fourth grade by using a longitudinal cross-lagged design. The sample was composed of 261 students assessed at the end of grades 2, 3, and 4. The results indicated that there is a reciprocal relation between listening comprehension and reading comprehension in every grade and that oral reading fluency and reading comprehension have a reciprocal relation only in the initial years of schooling, similar to the observed relation between oral reading fluency and word reading. The results are discussed considering their potential impact and the limitations of the study.